(untitled) (Baghdad Science Journal, 2021)
This work involves separating and studying the aminoacylase-1 (ACY1) of amniotic fluid from healthy pregnant, mainly one peak with higher activity has been isolated by DEAE-Cellulose ion exchange from the proteinous supernatant produced by deposition of proteins using ammonium sulfate (65%) after dialysis. The purification folds reaching to 19 folds also gave one protein peak when injected into the gel filtration column, a high ACY1 purity was obtained, with 38 folds of purification. It was found that the molecular weight of the isolated ACY1 was up to 46698 Dalton when using gel chromatography technique.The effect of ACY1 isolate was studied on rats with oxidative stress caused by lead acetate(LA) at 40 mg / kg body weight and compared with normal rats by measuring the selected biochemical parameters which included: Glutathione (GSH), malondialdehyde (MDA), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) through liver and kidney tissue examination. The results showed a significant increase in the levels of (MDA, AST, ALT) and a decrease in the level of GSH compared with the control group, Also it has been observed there that was a significant decrease in the levels of (MDA, AST, ALT) and high level of GSH when injecting the ACY1 isolate in a dose of 4 mg / kg of rat weight with LA at 40 mg/kg. The results of the tissue examination demonstrated high pathological changes in the liver tissue of rats treated with LA at 40 mg/kg of rat weight when compared with normal rats. The liver and kidney tissue improved when treated with isolate at 4 mg / kg rat weight and LA. These results demonstrate the role of ACY1 in protecting from oxidative stress then can reduce the severity of various diseases. Studying the effect of ACY1 isolated on rats with oxidative stress caused by lead acetate at a dose of 40 mg / kg body weight and compared with normal rats by measuring the selected biochemical parameters which included: Glutathione (GSH), malondialdehyde (MDA), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) as well as through liver and kidney tissue examination. The results showed a significant increase in the levels of (MDA, AST, ALT) and a decrease in the level of GSH compared with the control group, It was also observed that there was a significant decrease in the levels (MDA, AST, ALT) and high level of GSH when using the enzyme isolated in a dose of 4 mg / kg of rat weight with lead acetate at a dose of 40 mg/kg. The results of the tissue examination showed high pathological changes in the liver tissue of rats treated with lead acetate at a dose of 40 mg/kg of rat weight when compared with normal rats, and liver and kidney tissue improvement when isolated enzyme is administered at 4 mg / kg rat weight with lead acetate. These results demonstrate the role of isolated enzyme in protecting the body from oxidative stress then can reducing the severity of various diseases.